2022
DOI: 10.1371/journal.pbio.3001785
|View full text |Cite
|
Sign up to set email alerts
|

Anterior cingulate cortex causally supports flexible learning under motivationally challenging and cognitively demanding conditions

Abstract: Anterior cingulate cortex (ACC) and striatum (STR) contain neurons encoding not only the expected values of actions, but also the value of stimulus features irrespective of actions. Values about stimulus features in ACC or STR might contribute to adaptive behavior by guiding fixational information sampling and biasing choices toward relevant objects, but they might also have indirect motivational functions by enabling subjects to estimate the value of putting effort into choosing objects. Here, we tested these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 75 publications
0
4
0
Order By: Relevance
“…We found the neural correlates of enhanced set shifting in those neural circuits in the ACC and striatum of NHPs that are known to activate during guided exploratory behavior and information seeking (Bromberg-Martin and Monosov, 2020; Boroujeni et al, 2022; Jahn et al, 2023). Activity in the ACC, in particular, correlates with successfully exploring alternative options and gathering information about the value of options (Jahn et al, 2023).…”
Section: Discussionmentioning
confidence: 91%
“…We found the neural correlates of enhanced set shifting in those neural circuits in the ACC and striatum of NHPs that are known to activate during guided exploratory behavior and information seeking (Bromberg-Martin and Monosov, 2020; Boroujeni et al, 2022; Jahn et al, 2023). Activity in the ACC, in particular, correlates with successfully exploring alternative options and gathering information about the value of options (Jahn et al, 2023).…”
Section: Discussionmentioning
confidence: 91%
“…Moreover, feedback-related aMCC activity during a probabilistic learning task was associated with performance in a delayed memory task (Klein et al, 2007). In addition, ultrasound stimulation of the aMCC-homolog during a learning task in non-human primates reduced learning efficiency and prolonged information sampling (Banaie Boroujeni et al, 2022). Third, results from functional connectivity analyses revealed stronger aMCC connectivity with hippocampus and ventral striatum during early learning when feedback is highly informative, compared to later stages in learning (Klein et al, 2007).…”
Section: Decision Makingmentioning
confidence: 93%
“…Low‐intensity transcranial‐focused ultrasound stimulation (TUS) is gaining increasing attention due to the advantages of high spatial resolution and ability to target deep brain structures such as the basal ganglia (Nakajima et al., 2022), thalamus (Legon et al., 2018), anterior cingulate cortex and striatum (Banaie Boroujeni et al., 2022). Recent work has demonstrated that TUS could induce aftereffects at the stimulated site that persist beyond the period of stimulation (Nakajima et al., 2022; Samuel et al., 2022; Zeng et al., 2022; Zhang et al., 2021).…”
Section: Introductionmentioning
confidence: 99%